Análisis de los beneficios del uso comunicacional de las redes sociales digitales Facebook e Instagram como medio de posicionamiento de marca de las microempresas en Loja - Hidalgo Quizhpe, Andrea Rebeca (2020)
This research was carried out based on the analysis of the communicational use of digital social networks, specifically Facebook and Instagram as a means of brand positioning of 6 microenterprises in the city of Loja. This analysis was carried out in order to show the benefits that digital social networks provide to these microenterprises so that they can publicize their products and services, this form shows a greater number of people or potential customers, thus generating a better brand positioning. The types and characteristics of the content that is published in the digital social networks of these microenterprises are analyzed to find out if there are flaws and to look for solutions that allow them to improve their presence in them. The owners of the analyzed microenterprises have little knowledge about the use of the digital social networks Facebook and Instagram, what causes your pages to lack content that impacts and does not generate interest in your target audience.